Feasibility of establishing a veterinary marker to total residue in edible tissues with non-radiolabeled study using high-resolution mass spectrometry. (December 2022) - Tong, Wei; Huang, Rose; Zuo, Hong; Zarabadipour, Cyrus; Moore, Amanda; Hamel, Dietmar; Letendre, Laura
Abstract: Traditionally, in vivo metabolism and total residue studies in veterinary drug research were conducted using radiolabeled drug where information on metabolite profiles and marker residue to total residue ratio is obtained. The Veterinary International Conference on Harmonisation (VICH) guideline GL46 indicates that the metabolism and residue kinetics in food-producing animals may be documented by an alternative approach, one other than the traditional radiolabeled study. High-resolution mass spectrometry (HRMS) has been widely used in human pharmaceutical R&D from metabolite profiling and identification in early drug discovery to first-in-human (FIH) studies in development. Recent advances in data mining tools have greatly improved the metabolite profiling capability with HRMS. It is now routine to study metabolism using non-radiolabeled samples without missing any major metabolites. In the current paper, we explored the feasibility of conducting non-radiolabeled marker residue studies to obtain metabolism information using HRMS. Metabolite profiles of gamithromycin in edible tissues of sheep treated with 6 mg/kg body weight subcutaneous injections were obtained with HRMS. The semi-quantitative relationship between the level of gamithromycin and the total treatment-related residues was established by determining the percentages of extracted ion chromatograms for metabolites and parent compound residues in each tissue. Major components (gamithromycin and its metabolite, declad) were measured quantitatively using a validated liquid chromatography/tandem mass spectrometry (LC-MS/MS) method. Metabolite profiles in excreta were also obtained and the major components measured quantitatively with a LC-MS/MS method to ensure no major metabolite was missing. Combining previous knowledge of marker residue studies in cattle and swine, as well as an in vitro comparative metabolism study with metabolite data across various species, gamithromycin was designated as the marker residue in sheep edible tissues. The marker to total residue ratios were established using a combination of the semi-quantitative HRMS results and quantitative results with the major components: the marker residue and declad. The pros and cons of the HRMS method as well as the appropriate use of the method for marker residue studies are discussed. Highlights: Alternative approach with non-radiolabeled material to study the metabolism and residue kinetics was carried out according to VICH GL46. The marker to total residue ratios in sheep edible tissues were established using a combination of the semi-quantitative HRMS and quantitative - LC-MS/MS results for major residue components. The residue depletion study using this approach was successfully used to support the human food safety package for sheep in EU. The pros and cons of the HRMS method as well as the appropriate use of the method for marker residue studies are discussed.